Feed Intake, Nutrient Digestibility, Antioxidant Activity in Plasma, and Growth Performance of Male Dairy Cattle Fed Black Rice and Purple Corn Extracted Residue - R. Prommachart; J. Uriyapongson; A. Cherdthong; S. Uriyapongson (Tropical Animal Science Journal, 2021)
The study aimed to evaluate the impact of black rice and purple corn extracted residue (BPER) on feed intake, nutrient digestibility, growth performance, and antioxidant activity in male dairy cattle. The residue after extraction of anthocyanin from black rice and purple corn contains anthocyanin and phenolic acids. Several researchers found that anthocyanins and phenolic acids had antioxidant and antimicrobial functions in animals. Sixteen male dairy cattle (with average body weight of 160 ± 10.6 kg) were allotted in a completely randomized design (CRD) with 4 levels of black rice and purple corn extracted residue (BPER) at 0%, 2%, 4%, and 6% dry matter (DM) in total mixed ration (TMR). The TMR diets were fed ad libitum for 125 days. The daily DM intake, nutrient digestibility, growth performance, and plasma metabolites were measured. The results showed that BPER up to 6% had no effect on intakes of DM, organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF). Intake of ether extract (EE) increased with higher levels of BPER (p<0.05). The DM, OM, CP, NDF, and ADF digestibility were similar among treatments. The average daily gain (ADG) and feed per gain were similar among treatments. There was no effect of BPER on the concentrations of glucose, urea, total cholesterol, aspartate aminotransferase (AST), alanine aminotransferase (ALT), protein carbonyl, and antioxidant activity in the plasma. However, the malondialdehyde (MDA) concentrations in the plasma decreased (p<0.05) with the increased level of BPER, indicating that lower lipid oxidation compared to 0% BPER. It was concluded that BPER can be used up to 6% to reduce oxidative stress, without any negative effect on feed intake and nutrient digestibility.